Effect of fungicide spray and staking on diseases and disorders of tomato (Lycopersicon esculentum) - Bhardwaj, C L; Thakur, D R; Jamwal, R S (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the rainy season of 1991 and 1992 to study the effect of fungicide spray and staking on diseases and disorders of tomato (Lycopersicon Â esculentum Miller nom. cons.). Mid-June transplanted 'Roma' tomato under mid-hill sub humid climate of Bajaura showed that fungicide-spray schedules and staking increased the marketable fruit yield by 65.4 and 25.4% compared with the unsprayed control and no staking respectively. Both these operations decreased the yield of discarded fruit by 27.1 and 31.5% respectively. Still there was a loss of 7.4 tonnes/ha discarded tomato. The efficacy of fungicide application increased by 27% by adopting staking. Staking alone did influence the incidence of buckeye-rot [Phytophtora nicotanae van Breda de Haan var nicotianae (Dastur) Waterhouse], but not of other foliar diseases. Three sprays of mancozeb 75 WP @ 0.25% gave significantly better control of early blight caused by Altemaria solani (Ell. & Mart.) Jones & Grout and leaf spot caused by Septoria lycopersici Speg., and stabilized higher marketable yield. Two sprays of copper oxychloride 50 WP @0.25% proved better in reducing the incidence of buckeye-rot by 38%. The combined incidence of fruit-rot caused by Alternaria altemara (Fr.) Keis. and Sclerotium ralfsii Sacc., fruitborer [Helicoverpa armigera (Hubner)], end-rot (often due to deficiency of calcium) and sun-burn (physical injury due to contact of fruit with soil surface) was 14.9%.